The terrorist drift of anarchism in Spain: From the cult of freedom to violent action - Tejera Pinilla, Carmen (Clio. History and History Teaching, 2018)
This essay presents the status of the issue about anarchist terrorism from four monographies published between 1983 and 2013. This is a topic which has received little attention from historians. Revising this bibliography is interesting because it is a topic presented in an anecdotical and shallow way in most cases, with no relation with its ideological basis. This analysis shows some theories developed in last decades by historians as Avilés, Herrerín, Casanova and Núñez Florencio. Some authors propose comparative studies of the attacks in order to explain them as the result of a conspiration, instead of the traditional view of the individual terrorist. The article sets out if there is a estereotype of terrorist, lists the main attacks in the turn of the century and analyzes the theoretical basis of anarchism. Finally, it goes throught the Spanish terrorism and the police repression, that generated a bigger radicalisation ot anarchism in its violent trend.
Keywords: Anarchism; terrorism; violentaction; propaganda of the deed; magnicide